Researching educational barriers in participatory real-world labs: vocational training of refugees in rural counties in Germany - Thomas, Stefan; Albrecht, Pauline; Korntheuer, Annette; Bucher, Judith (Frontiers in Education, 2024)
As a result of the large-scale arrivals of refugees and migrants, Germany is facing the challenge of providing inclusive education pathways not at least for a successful integration into the labor market. In our research project laeneAs (Ländliche Bildugnsumwelten junger Geflüchteter in der beruflichen Ausbildung / The Rural Educational Environments of Young Refugees in Vocational Training), we focus on educational barriers and good practices within the vocational education and training system (VET) for refugees in rural counties. In particular, racism and discrimination are significant barriers to refugee participation in society and education. Our contribution addresses the following research question: How is educational inclusion discussed and defined in and through real-world labs among stakeholders in four rural districts: social workers, educators, policymakers, administration, and young refugees? We initiated real-world labs as a space for collaborative research, reflection, and development to promote inclusive pathways for young refugees in vocational education and training in four research sites. We used futures labs as a method to identify key challenges and develop action plans as an activating method with stakeholders and refugee trainees. Our data consisted of audio recordings of group discussions in the real-world future labs, which were analyzed using deductive content analysis. The analysis identified the following areas as important barriers to education and for practice transformation: 1) infrastructural and cultural barriers; 2) day-to-day problems in vocational schools and companies 3) restrictive immigration policies and regulations. Educational barriers are imbedded in a contradictory immigration regime with reciprocal effects so that refugee trainees have difficulties in completing their education and further their social inclusion. On the other side of this contradictory immigration regime, social work and social networks provide fundamental support in obtaining a vocational qualification.